Hubungan kelahiran prematur dengan penyakit jantung bawaan di RSUP Prof. Dr. R.D. Kandou Manado periode tahun 2013-2014 - Binalole, Vivi N.; Kaunang, Erling D.; Rampengan, Novie H. (e-CliniC, 2016)
Abstract: Preterm birth is all births before 37 completed weeks of gestation since the first day of a woman's last menstrual period. In the maturation of all organs of preterm birth has not been achieved so well that it may cause disruption, one of them is called the heart of congenital heart disease. Congenital heart disease is a problem with the heart's structure and function that is present at birth. The study aimed is to examine the relationship between preterm birth with congenital heart disease. This studied was conducted using observational analytic study design with a retrospective approach. The studied sample was children who were born Preterm in the Section of Child Health Prof. Dr R. D Kandou Manado diagnosed with congenital heart disease in 2013-2014. The study population numbered 353 children born prematurely, the sample fulfilled inclusion criteria are children born prematurely with CHD totaling 35 samples, and 30 samples were taken comparators. The assay used in this study is the Fisher Exact Test, produces a value p = 0.011 <Î± = 0.05, which indicates there is a significant relationship between preterm birth with congenital heart disease. Conclusion: There was a significant relationship between preterm birth with congenital heart disease. Keywords: Preterm birth, congenital heart disease Abstrak: Kelahiran prematur adalah semua kelahiran sebelum 37 minggu masa kehamilan sejak hari pertama haid terakhir seorang wanita. Pada kelahiran prematur kematangan semua organ belum tercapai dengan baik sehingga dapat menyebabkan gangguan, salah satu diantaranya yaitu jantung yang disebut PJB. Penyakit jantung bawaan (PJB) sendiri adalah permasalahan pada struktur jantung yang tampak setelah kelahiran. Tujuan penelititan ini adalah mengetahui hubungan antara kelahiran prematur dengan penyakit jantung bawaan. Penelitian ini dilakukan dengan menggunakan desain penelitian analitik observasional dengan pendekatan retrospektif. Sampel penelitian yaitu anak yang lahir prematur di Bagian Ilmu Kesehatan Anak RSUP Prof. Dr. R. D. Kandou Manado yang terdiagnosis PJB pada tahun 2013-2014. Populasi penelitian berjumlah 353 anak yang lahir prematur, sampel penelitian yang memenuhi kriteria inklusi yaitu anak yang lahir prematur dengan PJB berjumlah 35 sampel, dan diambil 30 sampel pembanding . Uji yang digunakan pada penelitian ini adalah Uji Fisher Exact, menghasilkan nilai p = 0,011 < Î± = 0,05, yang menunjukan ada hubungan yang bermakna antara kelahiran prematur dengan PJB. Simpulan: Ada hubungan yang bermakna antara kelahiran prematur dengan PJB. Kata kunci: Kelahiran prematur, PJB